Hydrocarbon Removal in Power Plant Plumes Shows Nitrogen Oxide Dependence of Hydroxyl Radicals. Issue 13 (5th July 2019) - de Gouw, J. A.; Parrish, D. D.; Brown, S. S.; Edwards, P.; Gilman, J. B.; Graus, M.; Hanisco, T. F.; Kaiser, J.; Keutsch, F. N.; Kim, S.‐W.; Lerner, B. M.; Neuman, J. A.; et al.
Abstract: During an airborne study in the Southeast United States, measured mixing ratios of biogenic hydrocarbons were systematically lower in air masses containing enhanced nitrogen oxides from power plants, which we attribute to increased concentrations of hydroxyl (OH) radicals within the power plant plumes. Plume transects at successively further downwind distances provide a decreasing gradient of nitrogen oxides (NOx ) concentrations, which together with the implied loss rates of isoprene, constrains the OH dependence on NOx . We find that OH concentrations were highest at nitrogen dioxide concentrations near 1–2 ppbv and decreased at higher and at lower concentrations. These findings agree with the dependence of OH on NOx concentrations expected from known chemical reactions but are not consistent with some studies reporting direct OH measurements higher than expected in regions of the atmosphere with low NOx (NO < 0.08 and NO2 < 0.46 ppbv) and high biogenic hydrocarbon emissions. Plain Language Summary: Hydroxyl radicals are the main chemical species that removes trace gases from the atmosphere. They determine the atmospheric lifetime of some greenhouse gases and chemicals involved with the destruction of the stratospheric ozone layer. Hydroxyl reactions also play an important role in air pollution chemistry. Measuring hydroxyl radicals is very challenging because of their high reactivity and low concentrations. Some recent measurements have shown unexpectedly high concentrations in relatively clean conditions. In this work, we indirectly estimated the dependence of hydroxyl radicals on the concentration of nitrogen oxides downwind from power plants in the Southeast United States. We observed that mixing ratios of isoprene, a reactive hydrocarbon released from deciduous trees to the atmosphere, were systematically lower in power plant plumes, caused by higher hydroxyl radical concentrations at the elevated nitrogen oxide concentrations. These findings can be explained by known chemical reactions but are not consistent with some studies that found unexpectedly high hydroxyl concentrations in relatively clean conditions. Key Points: Isoprene was found to be reduced in power‐plant plumes in the Southeast United States because of enhanced removal by hydroxyl (OH) radicals Observations at different downwind distances from two power plants allow the nitrogen‐oxide (NOx ) dependence of OH to be constrained The NOx dependence of OH is explained by known photochemistry, in contrast with some studies based on direct measurements of OH